تصميم خوارزمية استيفاء تحليل رقمي تفاضلي عالية الدقة - الشامي, إبراهيم (Latakia University Journal -Engineering Sciences Series, 2019)
تبحث هذه الورقة في تحليل و مقارنة دقة التوليد بخوارزميات الاستيفاء المستندة على التحليل الرقمي التفاضلي ، ويتم طرح خوارزمية جديدة تتصف بدقة توليد أعلى من جميع الخوارزميات المعروفة حالياً. تعتمد المقارنة على حساب معين مصفوفة الانتقال T ، حيث ترتبط الإحداثيات الحالية Pi بالإحداثيات الآتية Pi+1 بالعلاقة العودية Pi+1=T.Pi، ويكون بشكل عام . وتعتمد الخوارزمية المقترحة على فرض قيمة cosθ بحيث تساوي، وحساب sinθ بحيث يكون معين مصفوفة الانتقال أقرب ما يمكن للواحد الصحيح ، وتستخدم مصفوفة الانتقال في حساب إحداثيات أول نقطة مولدة، وتحسب إحداثيات باقي النقاط من علاقة هنرييه: { Pi+2= (2cosθ).Pi+1-Pi } i >0 . In this paper the writer presents a new algorithm for circular interpolation DDA. The accuracy of this algorithm is much higher than all others compared in this paper. The comparison in algorithms of interpolation depends on calculating a determinant of the rotation matrix T. We may obtain the following recurrence formula: , where Pi i>0 is an equidistance point sequence on circular arc and T is a rotation matrix: . Our method is based on imposing a value of cosθ as: (cosθ ) and calculating the value of sin where the determinant |T| equals unity. This results that: . We used cosθ and sinθ calculating the value of coordinates a single point which comes after the initial point directly. The rest of the interpolation points are calculated by Henrie's equation: { Pi+2= (2cosθ).Pi+1-Pi } i >0 .